Body fat distribution, fat-free mass and cardiovascular function in the UK Biobank - Oguntade, AS; Lacey, B; Taylor, H; Lewington, S (Oxford University Press, 2023)
Background: Excess adiposity and high body mass index have been associated with cardiac dysfunction and heart failure. However, the role of whole body imaging and independent associations of regional fat and fat-free mass on left ventricular and vascular function is unclear.